High Quality Image Steganography on Integer Haar Wavelet Transform Using Modulus Function - Prajanto Wahyu, Adi; Farah Zakiyah, Rahmanti; Nor Azman, Abu (Institute Of Electrical And Electronics Engineers Inc. (IEEE), 2016)
A high demand on digital information in the last decade raises serious concern to protect its secrecy. Digital steganography hides the presence of a message in order to avoid an adversary attention. An image is the most popular medium of steganography. Hiding data into wavelet coefficients are able to maintain image quality. An Integer Haar Wavelet Transform (IHWT) is a method that transforms a 2D image into wavelet coefficients. IHWT which is derived from Discrete Wavelet Transform (DWT) can been suited to a human visual system (HVS). Moreover, IHWT coefficients are represented in finite precision which avoids the floating point problem of DWT. This paper proposes on improving the quality of stego image from the previous method that uses coefficient difference (CD) on IHWT. Instead of using CD that calculates the difference between coefficients, this paper uses the modulus function on two adjacent coefficients to embed the message. The proposed method has successfully reduced the effect on adjusted coefficients between two adjacent coefficients. This technique has led to an improvement on the stego image quality. The experimental results shows that the proposed method achieved higher imperceptibility than the previous method.